The research field of Social Innovation: Deriving an updated view on the field through a co-citation analysis - Andreas Fazekas; Daniel J. Kruse; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2020)
This paper presents a thorough analysis of the research field of Social Innovation (SI). It seeks to contribute to the understanding of how this dynamic research field has developed since the early 2000s by addressing three main topics. First, an analysis of the current intellectual structure of the field derived through a co-citation analysis of 1.184 relevant scientific documents is presented. Second, the role of public institutions for SI is discussed. Third, the theoretically established link between Open Innovation and Social Innovation is examined. The results show that four main cluster exist defining the research field of SI. These clusters are: Social Entrepreneurship, Partnerships and Interaction, Theoretical Foundation and Change and Transition Management. The analysis indicates that a unifying literature body has been established and is commonly accepted in academia. Moreover, the results confirm the strong link to the practice and highlight the relevance of SI for various stakeholder. Based on these results it can be concluded that the research field of SI has developed from being a small and not independent area to a complex, mature, established and independent research field within the last two decades.
Keywords: 330; Social Innovation; Co-Citation Analysis; Intellectual Structure; Social Innovation Definition; Business Innovation; Literature Review; Social Entrepreneurship; Bibliometrics